Thermal Pyrolysis of Used Lubricant and Cooking Oil Mixtures - Nazarudin Nazarudin; S.P. Amalia; Afrida Afrida; Ulyarti Ulyarti (Postgraduate, University of Mataram, 2021)
Pyrolysis is the one solution to recycle hydrocarbon-based waste material such as used lubricant and cooking oil. The aim of this research was to determine the effect of temperature and sample ratio on the liquid yields of a mixture of used lubricant and cooking oil. The semi batch reactor was used with a constant nitrogen flow rate of 5 mL/min. Three different ratios of sample mixture were applied in this experiment: 0.5:1, 1:1, and 1.5:1, and three different temperatures: 4000C, 4500C, and 5000C. The thermal pyrolysis of a mixture of used lubricant and cooking oil was deemed as the most effective pyrolysis to produce liquid fraction was obtained from reaction condition with the sample mixture ratio of 0.5:1 at 5000C. At this reaction condition, the liquid yield was 58.90% which consist of 64.12% were C1-C3 and 29.54% were C5-C15. Liquid fraction is predicted to increase as the temperature increase and the ratio of used lubricant to cooking oil decrease. When the ratio is increased , more gas fraction is produced.